Pushing the Boundaries of the Universe: The Criticisms of Peripatetic Cosmology in Hikmat al-ishrāq and its Commentaries - İshak Arslan (Nazariyat: Journal for the History of Islamic Philosophy and Sciences)
In this article, focused on the criticism of Suhrawardi who is the founder of the Ishrāqi School, four cosmological problems pointed out in the Hikmat al-Ishrāq are analyzed. These problems, which allow for the comparative analyses of these two systems in terms of differences and similarities, are respectively, the limits and the order of the universe, the location and the function of the sphere of fixed stars, retrograde motion, and the state of the Sun and the Moon. Although both systems take as their basis jointly the emanation model, the indications, and criticisms posed by Suhrawardi in regards to the aforementioned problems and in addition, the interpretations of these criticisms by the commentators of the Hikmat al-Ishrāq will be discussed. Finally, the prospective effects and value of this discussion on modern cosmology are among the fundamental questions raised in this article.